Institutional quality and economic performance in the Caribbean and Latin America - VEGA CENTENO GAMARRA, Jose Emilio (KDI School, 2016)
This study employed panel data analysis for the period between 1996 and 2010, to ascertain the overarching institutional constituent in explaining output per capita differences across the Caribbean and Latin America. It was inferred from the regression results that of all the investigated institutional components, the control of corruption index was not only the most robust in all the specified empirical models, but it was invariably positive and statistically significant. More so, a combination of corruption control plus the voice and accountability indices, elicited a robust and statistically significant correlation between it and real GDP Per Capita. Akin to Gaskins and Kock (2013), the latter results manifest the role voice and accountability plays, in not only aiding instituted corruption control measures, but also to attenuate and eradicate the adverse effects of the vice. In consequence, a telling case is made for strengthening the institutions that control corruption, in order to improve the Caribbean and Latin America`s living standards. The latter not only lends empirical credence to Mario Vargas (2015) contention that corruption is Latin America`s top problem, but it also shows that reining it in, among other things is vitally important. Also, this underscores Brunt (2007)`s overarching question regarding “which particular institutions matter for economic growth.” Policy wise, efforts expended in either reducing or eradicating corruption can benefit from increased levels of voice and accountability, akin to Kock and Gaskins (2014). Finally, a proxy of collective institutional quality, constructed and invoked as a composite index, also exerted benign effects on living standards, hence accentuating the significance of strengthening institutional quality, especially when purging the markets of functional inefficiencies.
Thesis(Master) --KDI School:Master of Development Policy,2016